Проблеми розробки методики розрахунку перекосних навантажень кранів - Коваленко, Валентин Олександрович; Стьопочкін, Володимир Львович; Турчин, Ольга Володимирівна; Гнатенко, Григорій Олександрович; Рубашка, Володимир Петрович; Стрижак, Всеволод Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2025)
В статті розглянуті основні теоретичні припущення, прийняті в стандартних методиках обчислення перекосних навантажень. Обговорюються шляхи вирішення існуючих проблем: додаткове використання двоточкового опирання моделі, уточнення емпіричних формул для сили зчеплення колеса з рейкою та інші. Зазначені уточнення потребують використання засобів програмування, що на сьогодні є прийнятним. Результати можуть бути використані при розробці удосконаленої методики визначення перекісних сил, що діють на крани.

The article discusses the main theoretical assumptions used in methods for calculating skewing loads acting on crane. These loads are caused by sideways movements during operation and lead to numerous negative consequences. The corresponding lateral forces acting on the wheels are standardized according to the current standards – DSTU EN13001-2 and DSTU EN15011. The existing problems, limitations of these approaches, and ways to overcome them are discussed, primarily the use of a two-point support model along with a single-point one, refinement of empirical formulas for the force of wheel adhesion to the rail, and expansion of the number of forces applied in the calculation combination. These refinements and additions require the use of programming tools, which is acceptable today. The results can be used in the development of an improved methodology for determining the lateral forces acting on cranes.
Problems of developing a methodology for crane skewing loads calculating
Keywords: кран; перекіс; бічні сили; стандарт; модель; методика; crane; skew; lateral forces; standard; model; methodology